2020
DOI: 10.1101/2020.09.18.20197640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved symptoms following bumetanide treatment in children aged 3 to 6 years with autism spectrum disorder via GABAergic mechanisms: a randomized, double-blind, placebo-controlled trial

Abstract: With the drug therapy for the core symptoms of autism spectrum disorder (ASD) currently limited, here we reported a randomised, double-blind, placebo-controlled trial to investigate the efficacy, safety, and potential neural mechanism of bumetanide in children with ASD aged 3 to 6 years old. In this trial, 120 children with ASD were 1:1 randomly assigned to receive 0.5 mg bumetanide or placebo orally twice daily for 3 months. The primary outcome was the score reduction of Childhood Autism Rating Scale (CARS) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…See Figure 2 for the results on the risk of bias of these included studies. Three studies ( 18 , 19 , 25 ) clearly used the method of random sequence generation and were considered to be low risk. Three studies ( 17 , 21 , 26 ) failed to explain their random sequence generation and were rated as unclear risk.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…See Figure 2 for the results on the risk of bias of these included studies. Three studies ( 18 , 19 , 25 ) clearly used the method of random sequence generation and were considered to be low risk. Three studies ( 17 , 21 , 26 ) failed to explain their random sequence generation and were rated as unclear risk.…”
Section: Resultsmentioning
confidence: 99%
“…Their results revealed that bumetanide improved the core symptoms of ASD and had a promising benefit/risk ratio, especially when administered twice per day at a dose of 1.0 mg. Positive results of bumetanide in children with autism have also been reported in one study from Sweden and two studies of the same team from China (19)(20)(21). Moreover, the two Chinese studies tried to assess possible neuropharmacological mechanisms of bumetanide in young children with ASD by magnetic resonance spectroscopy (MRS).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations